Usulan Peningkatan Kualitas Pelayanan Pasien Menggunakan Metode Importance Performance Analysis (IPA) dan Potensial Gain In Customer Value (PGCV) di Puskesmas XYZ - Hanifah, Hanifah; Lubis, Fitriani Surayya; Harpito, Harpito; Hartati, Misra; Nofirza, Nofirza (Universitas Batanghari Jambi, 2025)
This study aims to analyze the quality of patient services at the XYZ Health Center and determine the level of importance that is useful for obtaining priorities for improving the quality of health services and making proposals for improving the quality of health services. The methods used are Importance Performance Analysis (IPA) and Potential Gain in Costumer Value (PGCV). The problems in this study are that the time for examination and consultation with doctors is too short due to the large number of queues, officers are less friendly in serving patients, information about drugs and diagnoses of diseases explained by officers is less clear due to patients who are in a hurry and do not read existing information and patients wait too long to be examined for more than an hour. The results of the calculation of the IPA and PGCV methods show that the attributes that need to be improved are P6, P8, P14 and P15. Recommendations for improvement are adding doctors, synchronizing schedules between the puskesmas and the doctors concerned, rewarding health workers and giving sanctions in the form of reprimands for officers who are not polite and friendly and reducing waiting times and delays in providing health services to patients.